Answers:
Equation is ![(x+1)^2 + (y+2)^2 = 25](https://tex.z-dn.net/?f=%28x%2B1%29%5E2%20%2B%20%28y%2B2%29%5E2%20%3D%2025)
Center is (-1, -2)
Radius = 5
===========================================
Work Shown:
![x^2+2x+y^2+4y=20\\\\(x^2+2x)+(y^2+4y)=20\\\\(x^2+2x+1)+(y^2+4y)=20+1\\\\(x^2+2x+1)+(y^2+4y+4)=20+1+4\\\\(x+1)^2 + (y+2)^2 = 25\\\\](https://tex.z-dn.net/?f=x%5E2%2B2x%2By%5E2%2B4y%3D20%5C%5C%5C%5C%28x%5E2%2B2x%29%2B%28y%5E2%2B4y%29%3D20%5C%5C%5C%5C%28x%5E2%2B2x%2B1%29%2B%28y%5E2%2B4y%29%3D20%2B1%5C%5C%5C%5C%28x%5E2%2B2x%2B1%29%2B%28y%5E2%2B4y%2B4%29%3D20%2B1%2B4%5C%5C%5C%5C%28x%2B1%29%5E2%20%2B%20%28y%2B2%29%5E2%20%3D%2025%5C%5C%5C%5C)
center = (h,k) = (-1,-2)
radius = 5
-----------------------------
Explanation:
I grouped up the x and y terms separately. Then I added 1 to both sides to complete the square for the x terms. I cut the 2 from 2x in half, then squared it to get 1. In the next step, I cut the 4 from 4y in half to get 2, which squares to 4. So that's why I added 4 to both sides to complete the square for the y terms.
Each piece is factored using the perfect squares factoring rule which is a^2+2ab+b^2 = (a+b)^2
The last equation is in the form (x-h)^2 + (y-k)^2 = r^2
We can think of x+1 as x - (-1) to show that h = -1
Similarly, y+2 = y-(-2) = y-k to show that k = -2
The center is (h,k) = (-1,-2)
The radius is r = 5 because r^2 = 5^2 = 25 is on the right hand side in the last equation above.